Stimulating organizational learning through networks and communities - Donaldson, Alison; Lank, Elizabeth; Maher, Jane (Henry Stewart Talks, 2009)
Understanding learning and change as social and emergent processes, What are communities and networks?, How do communities of practice contribute to organizational performance?, Extending the organization's reach, Macmillan case study, What it takes to make communities work, Challenges of working through communities, Challenges of evaluating the contribution of communities, Benefits of working through communities
Archived at 2025/05/28